Nonremovable, windowed, fiberglass cast boot in the treatment of diabetic plantar ulcers: Efficacy, safety, and compliance - HA VAN, Georges; SINEY, Hubert; HARTMANN-HEURTIER, Agnes; JACQUEMINET, Sophie; GREAU, Francoise; GRIMALDI, André (Diabetes care, 2003)
To compare the efficacy, safety, and compliance of a nonremovable fiberglass cast boot and off-loading shoes in the treatment of diabetic plantar ulcers. Patients (n = 93) with noninfected, nonischemic plantar ulcers were included in this prospective nonrandomized study. Treatment used a nonremovable fiberglass cast boot for longer standing and deeper ulcers (n = 42) and a half shoe or heel-relief shoe for other ulcers (n = 51). We evaluated off-loading therapy, compliance, and complications in both groups. The healing rate was significantly higher with the cast boot than with the off-loading shoe (81 vs. 70%, P = 0.017), with healing times of 68.6 +/- 35.1 vs. 134.2 +/- 133.0 days, respectively, and hazard ratio 1.68 (95% CI 1.04-2.70); complete compliance with treatment was 98 vs. 10% (P = 0.001), respectively. Secondary osteomyelitis developed in 3 patients in the cast boot group and 13 patients in the off-loading shoe group (P = 0.026). A nonremovable fiberglass cast boot was effective in healing diabetic plantar ulcers and in decreasing the risk of secondary osteomyelitis. The cast boot forced compliance with off-loading, thus promoting healing.